REDEFINISI PETANI: DISKURSUS INDONESIA VIS-A-VIS BARAT - M. Gunardi Judawinata; Iwan Setiawan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
In Indonesia, the rising rate of agricultural land conversion and soil degradation, decreasing agricultural exchange rates, advancing technological and cultural development, and expanding innovations in planting mediums and farming approaches, have blurred the definition of a peasant. Does the same phenomenon happen worldwide? This paper aims to set the evolution of the definition of a peasant in Indonesia globally. This study departed from the constructivism paradigm, which used a hermeneutics approach and literature study method. More than 50 literature from the past century were studied. We found that in Indonesia, the definition of the peasant has not been strongly justified from many perspectives (experts, institutions, communities), which created disparities in space and time contexts. While peasant’s global definition tends to be constant as it acts as the centre of the proposition just like other professions. Diversities in commodities, planting systems, and the bargaining position of farming as economic activity caused the specification of peasant’s definition in Indonesia. Thus, the definition of the peasant is still “wild” without strong boundaries. As one of the former colonial countries, Indonesia cannot be separated from its colonial inheritance, which affected the media and corporations. We conclude that the reconstruction of peasants’ definitions and praxis becomes a necessity because the biases of the paradigm and characteristics of peasants have made peasants lose their autonomy, sustainability and sense of humanity (humanism). The definition of peasant is not limited to space and land occupied, it has not been agreed upon as a profession and the label is used openly.